Influence of mesenchymal stem cells derived from bone marrow of children with oncohematological diseases on proliferation and self-renewal of hematopoietic progenitor cells in vitro - Isaikina, Ya.; Shman, T. (Experimental Oncology, 2008)
To test the ability of cultured mesenchymal stem cells (MSCs) from bone marrow (BM) of children with oncohematological diseases after chemotherapy and radiation to support proliferation and self renewal of hematopoietic cells in vitro. Methods: BM samples of 8 patients and 9 healthy children-donors used for MSCs preparation applying techinque of expansion in vitro. CD34+ cells were isolated from BM of donors. The ability of MSCs to maintain hematopoietic stem cells (HSCs) proliferation was tested in semisolid methylcellulose medium and in liquid long-term-culture (LTC) medium. Results: The presence of MSCs derived from BM of patients in methylcellulose medium induced 2-fold increase of the number of commited myeloid progenitors without cytokines, 7-fold increase together with growth factors and 14-fold increase of the amount of earlier pluripotent hematopoietic precursor cells (CFU-GEMM) compared to expansion of HSCs without MSCs and cytokines. The presence of MSCs layer of patients in liquid LTC medium significantly promoted the hematopoietic cells proliferation rate, measured on 7th, 14th and 21st day. The total number of cells was multiplied 161.2-fold on 21st day as compared to 116.4-fold without MSCs layer. In the presence of MSCs layer, we detected the increase of proportion of bipotent CFU-GM precursors from 4% to 11% and pluripotent CFU-GEMM precursors from 0.1% to 0.6% in population of HSCs. In both types of experiments the capacity of patients’ MSCs to support HSCs proliferation and self renewal was the same as for healthy donors’ MSCs. Conclusion: In this study, МSCs were isolated from BM of children with malignancies after high-dose chemotherapy or radiation. The ability of these MSCs to maintain hematopoiesis in vitro was tested. It was shown that co-transplantation of autologous MSCs is a good way to improve hematopoietic stem cells engraftment and reduce a period of granulocytopenia after autologous HSCs transplantation in case of insufficient CD34+ cell number in autologous transplant. Цель: исследовали способность культивируемых in vitro мезенхимальных стволовых клеток (МСК), выделенных из костного
мозга детей со злокачественными новообразованиями, получавших в качестве лечения высокодозовую полихимиотерапию,
поддерживать гемопоэз in vitro. Материалы и методы: МСК выделяли и наращивали из проб костного мозга 8 пациентов
и 9 здоровых доноров детского возраста. CD34+ клетки выделяли из проб костного мозга доноров. Были поставлены
эксперименты по совместному культивированию МСК и CD34+ клеток в среде метилцеллюлозы и в среде для долгосрочного
культивирования с добавлением цитокинов и при их отсутствии. Результаты: в метилцеллюлозной среде наличие МСК
пациентов увеличивало количество коммитированных миелоидных предшественников в 2 раза, МСК совместно с ростовыми
факторами стимулировало пролиферацию этого типа клеток в 7 раз, а полипотентных предшественников — в 14 раз. При
долгосрочном культивировании с цитокинами на слое МСК общее количество ГСК на 21-й день возростало в 161,2 раза. При
пролиферации CD34+ клеток в среде с МСК содержание бипотентных КОЕ-ГМ повысилось с 4 до 11%, а полипотентных
КОЕ-ГЭММ — с 0,1 до 0,6%. В экспериментах по экспансии CD34+ клеток результаты при использовании в качестве
фидерного слоя МСК пациентов или МСК доноров статистически не отличались. Выводы: проведенные исследования
позволяют сделать вывод о том, что МСК из костного мозга пациентов со злокачественными новообразованиями обладают
достаточным функциональным потенциалом для пролиферации и самоподдержания ГСК. Ко-трансплантация аутологичных
МСК при аутотрансплантации ГСК с низким содержанием CD34+ клеток в трансплантате может являться перспективной
для сокращения периода восстановления гемопоэза в ранний посттрансплантационный период.